Towards a theology of the Psalm titles: The Davidic voice and the totus Christus - Balfour, Rory J. (Scottish journal of theology, 2024)
This article explores the ways in which the thirteen ‘biographical superscriptions’ which are found throughout the Psalter contribute to the blending of the Davidic voice which they invoke and the corporate voice of the community which receives them. It suggests that by receiving these thirteen Psalms, the canonical community enters an intensive identification with David and participates in the Davidic life and experience. Once this is established, the discussion turns to examine these insights in a Christian theological context in conversation with Augustine's totus Christus principle. It is suggested that the hermeneutical situation created by the biographical superscriptions provides a way for the totus Christus principle to be re-invoked in contemporary interpretation.